Life skills development in physical education: A self-determination theory-based investigation across the school term. (July 2020) - Cronin, Lorcan; Marchant, David; Johnson, Laura; Huntley, Emma; Kosteli, Maria Christina; Varga, Joseph; Ellison, Paul
Abstract: Objectives: Grounded in self-determination theory (SDT), the main aim of this study was to examine the longitudinal associations between teacher autonomy support, students' basic psychological need satisfaction and life skills development in physical education (PE). Design: This study employed a two-wave longitudinal research design. Method: Students ( N  = 266, M age = 12.94 years, SD  = 0.70) completed measures assessing perceived autonomy-supportive teaching, need satisfaction (autonomy, competence, and relatedness), and life skills development in PE (teamwork, goal setting, social skills, problem solving and decision making, emotional skills, leadership, time management, and interpersonal communication). Data collections took place during week 6 (timepoint 1; T1) and week 15 (timepoint 2; T2) of the autumn school term. Results: Cross-lagged panel analyses showed that T1 teacher autonomy support did not significantly predict students' three basic psychological needs, total need satisfaction or life skills development at T2. Students' T1 total need satisfaction positively predicted their development of all eight life skills at T2. Additionally, students' T1 autonomy satisfaction positively predicted their teamwork, social skills, emotional skills, leadership, and interpersonal communication skills at T2, T1 competence satisfaction positively predicted students' teamwork skills at T2, and students' T1 relatedness satisfaction positively predicted their social skills at T2. Conclusions: Providing partial support for SDT, the findings highlighted that satisfaction of students' three basic psychological needs had some positive effects on students' life skills development in PE. As such, a climate that satisfies students' basic psychological needs should help to develop their life skills in PE. Highlights: Total need satisfaction at week 6 positively predicted all eight life skills at week 15. Week 6 autonomy satisfaction positively predicted 5 of the 8 life skills at week 15. Competence satisfaction at week 6 positively predicted week 15 teamwork skills. Relatedness satisfaction at week 6 positively predicted week 15 social skills. Week 6 teacher autonomy support did not significantly predict week 15 need satisfaction.